Comprehensive Physiology 2015
DOI: 10.1002/cphy.c150018
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Functions of Rnd 3/ RhoE

Abstract: Rnd3, also known as RhoE, belongs to the Rnd subclass of the Rho family of small GTP-binding proteins. Rnd proteins are unique due to their inability to switch from a GTP-bound to GDP-bound conformation. Even though studies of the biological function of Rnd3 are far from being concluded, information is available regarding its expression pattern, cellular localization, and its activity, which can be altered depending on the conditions. The compiled data from these studies implies that Rnd3 may not be a traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 152 publications
(196 reference statements)
0
60
1
1
Order By: Relevance
“…16 In addition, in HCC, RND3 has also been proposed as either an oncogene or tumor suppressor gene in other cancer types. 13,18 In the present research, we rst veried that miR-182-5p and miR-96-5p increased HCC cell mobility, proliferation and cisplatin resistance partially by targeting RND3. Using a selective ROCK1/2 kinase inhibitor, YC-S 7001, as well as specic knockdown of ROCK1 and ROCK2, we found that both ROCK paralogs are involved in the HCC cell mobility-promoting effect of RND3 knockdown.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…16 In addition, in HCC, RND3 has also been proposed as either an oncogene or tumor suppressor gene in other cancer types. 13,18 In the present research, we rst veried that miR-182-5p and miR-96-5p increased HCC cell mobility, proliferation and cisplatin resistance partially by targeting RND3. Using a selective ROCK1/2 kinase inhibitor, YC-S 7001, as well as specic knockdown of ROCK1 and ROCK2, we found that both ROCK paralogs are involved in the HCC cell mobility-promoting effect of RND3 knockdown.…”
Section: Introductionmentioning
confidence: 55%
“…RND3 (Rho Family GTPase 3, also named RhoE) is a member of the RND protein subgroup belonging to the Ras homologous (Rho) family of GTPases although the RND proteins exhibit no GTPase activity. 12,13 Mechanistically, RND3 was found to competitively bind with Rho Associated Coiled-Coil Containing Protein Kinase 1 (ROCK1), preventing the activation of the latter by Ras Homolog Family Member A (RhoA) although the existence of RhoA-ROCK1-independent activity of RND3 has also been anticipated. 13 The clinical signicance of RND3 as a tumor suppressor gene in HCC was rst reported by Luo et al, who documented a signicant association between RND3 downregulation and HCC progression, resulting in patients' shortened survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in depth understanding of the molecular mechanisms and functions of RND3 in different tissues is required to identify novel therapeutic targets for the diagnosis and treatment of human diseases (Jie et al, 2015). RND3 plays a complex role in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most members of the Rho family can cycle by the ratio of an active, GTP-bound conformation and an inactive, GDP-bound conformation, and GDP/GTP exchange process is regulated by several classes of regulators, including GDP/GTP exchange factors (GEFs) and GTPase-activating proteins (GAPs) (David et al, 2012). But RND3 (also known as RhoE), a unique member of the Rnd subfamily, is found that it do not hydrolyze GTP, and thus remains constitutively active upon expression without regulation by GEFs/GAPs cycling (Jie et al, 2015). Foster et al (1996) firstly cloned RND3 which was shown to display no detectable GTPase activity, similar to RND1 and RND2, indicating that RND3 has a different manner in which to regulate its activity.…”
Section: Introductionmentioning
confidence: 99%